POLA TANAM DAN SISTEM SILVIKULTUR PADA SKEMA PERHUTANAN SOSIAL DI KULON PROGO, D.I. YOGYAKARTA - Lestari, Puji; Utomo, Singgih; Prasetyo, Eko; Maulana, Ahdiar Fikri; Ngadianto, Agus; Qoyriah, Mufidatul; Lanangjati, Hafiz Satrio; Anggraeni, Cynthia (Universitas Pattimura, 2024)
Social forestry is a scheme chosen by the government to improve community welfare by providing legal access to communities to manage forests. One of the social forestry schemes implemented in Kulon Progo is Community Forestry. This scheme has great potential to be developed with a multi-use forestry management model. Therefore, a review of the silvicultural aspect is needed to understand the forest management model currently implemented. This research aims to identify tree species, planting patterns and silvicultural systems implemented by Community Forestry at Production Forests in Kulon Progo. The research was conducted from August to October 2023 in Plot 17 and Plot 19 of RPH Kokap, BDH Kulon Progo-Bantul. Observations were made by making measurement plots of 20 m x 40 m of each plot and then recording the name of tree species, coordinates, height, diameter, height without branches, and canopy width. The data were then analyzed using Spatially Explicit Individual-based Forest Simulator (SexI-FS) software version 2.1.0. to see the projected planting pattern. The results of the research showed that tree species planted in the Community Forestry were teak (Tectona grandis), acacia (Acacia mangium), mahogany (Swietenia macrophylla), eucalyptus (Eucalyptus sp.), paperback (Melaleuca leucadendron), and jackfruit (Artocarpus heterophyllus ). These species were planted using a mixed planting pattern with the silviculture system of selective logging with artificial regeneration.